Chemical composition and Antioxidant capacity of Spartium junceum grown in Lebanon - Rammal, Hassan; Zahreddine, Hawraa; Hijazi, Akram (Jour Med Resh and Health Sci, 2021)
The importance of Spartium junceum L. grown in Lebanon was investigated in this study. The chemical composition of three different S. junceum extracts (methanolic, water, and methanolic/water extracts) from different parts of the plant (stem, flower and legume) was determined using phytochemical screening analysis. Then the in vitro antioxidant capacity of these extracts was evaluated using the DPPH test. The obtained results revealed the presence of different metabolites such as phenols, flavonoids, alkaloids among others in the different prepared extracts from the studied parts of this plant. The methanolic extract exhibited a significant antioxidant activity compared to the water and water/methanolic extracts. On the other hand, a significant antioxidant activity has been noticed for these parts mainly with the methanol extract. Therefore it was lower in water and water/methanol extracts.